Foreign Body Inside the Tunnel: A Rare Cause of Acute Cubital Tunnel Syndrome - Yildiran, Gokce; Sutcu, Mustafa; Akdag, Osman; Tosun, Zekeriya (The Surgery Journal, 2019)
Foreign bodies are common entities found in hand surgery practice. However, they are a very rare cause of the acute cubital tunnel syndrome. A 48-year-old male patient was consulted for cubital tunnel symptoms after 2-day unconscious state in the intensive care unit. The ulnar nerve was explored, a piece of glass was removed inside the cubital tunnel, and the nerve was repaired. However, compression neuropathy symptoms due to the acute trauma are interesting. Nerve laceration with a foreign body should be considered in acute-onset cubital tunnel syndrome, in which the foreign body history of a trauma patient cannot be determined explicitly.
Keywords: acute; cubital tunnel syndrome; foreign body